Postmortem Metabolic, Physicochemical, and Lipid Composition Changes in Litopenaeus vannamei in Response to Harvest Procedures. Issue 9 (21st October 2017) - Zamora-Méndez, Saúl; Robles-Romo, Arlett; Marin-Peralta, Erica; Arjona, Olivia; Apún-Molina, Juan P.; Beltrán-Lugo, Ana I.; Palacios, Elena; Racotta, Ilie S.
ABSTRACT: Ante-mortem stress is recognized as one of the factors that could reduce shelf life in fish, although this topic has been scarcely addressed in crustaceans, particularly in cultivated penaeid shrimp where common harvest practices involves stressful conditions such as chasing, emersion, and confinement. This study analyzes indices of freshness in shrimp in response to such practices before storage in ice for six days. During ice storage, several indicators follow the typical postmortem pattern, although most of them (hypoxanthine, change in pH, and color) did not reach critical levels at day 6. Adenosine-5'-triphosphate (ATP) and degradation products (adenosine monophosphate, AMP, and inosine monophosphate, IMP), as well as several indicators of freshness (pH, expressible water, hardness, color, and the overall fatty acid composition) were not significantly affected by harvest. Other variables such as lower springiness, higher hypoxanthine, lipid hydroperoxides, and 20:4n-6/20:5n-3 ratio were observed in shrimp subjected to common harvest practices. However, under the current conditions of harvesting, these effects were marginal and probably do not substantially affect meat quality for human consumption, but care should be taken at higher environmental temperatures (e.g. harvest in summer) and for a duration of ice-storage over 6 days.